Regulatory T cells expressing FOXP3 and low CD25 in common variable immunodeficiency : unsupervised analysis of a flow cytometry study - Martins, Carolina Marques (2022)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2021